2003
DOI: 10.1093/nar/gng060
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of mitochondrial DNA copy number in human skeletal and cardiac muscle by a PCR-based assay: lack of change of copy number with age

Abstract: Deletions in mitochondrial DNA (mtDNA) accumulate with age in humans without overt mitochondriopathies, but relatively limited attention has been devoted to the measurement of the total number of mtDNA molecules per cell during ageing. We have developed a precise assay that determines mtDNA levels relative to nuclear DNA using a PCR-based procedure. Quantification was performed by reference to a single recombinant plasmid standard containing a copy of each target DNA sequence (mitochondrial and nuclear). Copy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
209
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(228 citation statements)
references
References 26 publications
17
209
2
Order By: Relevance
“…[22][23][24][25] For a given chromosomal region, short reads mapped to the region were retrieved from the BAM file at the FTP site of the 1000 Genomes Project 26 using samtools. 27 This was done for the whole mtDNA region and the autosomal regions; the numbers of short reads in the two regions were used to compute mtDNA/nDNA.…”
Section: Estimation Of Mtdna Copy Numbermentioning
confidence: 99%
“…[22][23][24][25] For a given chromosomal region, short reads mapped to the region were retrieved from the BAM file at the FTP site of the 1000 Genomes Project 26 using samtools. 27 This was done for the whole mtDNA region and the autosomal regions; the numbers of short reads in the two regions were used to compute mtDNA/nDNA.…”
Section: Estimation Of Mtdna Copy Numbermentioning
confidence: 99%
“…Although the literature is sparse and conflicting, animal studies have shown an increase in mtDNA copy number with age in several organs. [22][23][24] Regarding the mtDNA 4977 mutation, one might speculate that it may be a marker of either survival or aging. Although there is a large body of literature associating the mutation with aging and age-related pathology, there is little or no evidence to impute a causal role.…”
Section: Discussionmentioning
confidence: 99%
“…Most somatic cells contain approximately 10 3 mitochondria (Giles et al, 1980;Barritt et al, 1999). The actual amount depends on such factors as their cell's metabolic activity and intracellular spatial organization (configuration) of cytoskeleton and membrane skeleton microfilament network; also their ultrastructuro-functional specialization within the framework of both cytodifferentiation and exactly defined tissue-and organ-related histological topography and tissue-specific nuclear DNA and mtDNA gene expression (transcriptional activity) patterns (Moyes et al, 1998;Garesse and Vallejo, 2001;Gahan et al, 2001;Smeitink et al, 2001;Miller et al, 2003;Takeda et al, 2003). In most types of somatic cells that are the source of nuclear donors in the cloning procedure, the number of mtDNA molecules ranges from about 2 × 10 3 to about 5 × 10 3 copies, i.e.…”
Section: The Causes Of Mtdna Heteroplasmy Induction In Somatic and Emmentioning
confidence: 99%